PENGEMBANGAN KEMAMPUAN PEMAHAMAN MATEMATIK MENGGUNAKAN MOODLE DENGAN DISCOVERY LEARNING DALAM PEMBELAJARAN MATEMATIKA SECARA DARING - Evi Widianingrum; Jayanti Putri Purwaningrum (Jurnal Riset Pembelajaran Matematika, 2021)
This study is motivated by the ability to understand mathematics learning (understanding) students are still low, both junior high school. The ability to understand mathematics (understanding) in online learning needs to be developed for students to be able to understand the explanation of mathematical material. In online learning, many students find it difficult to implement learning. To overcome this, online learning with the ability to understand mathematics requires appropriate media and learning models in the learning process to be more effective. The alternative learning media used is Moodle-based media. With Moodle-based media, students will find it easier in the learning process. Online, mathematics learning can be accessed anywhere so that it is effective and flexible. Meanwhile, the learning model applied is the discovery learning model. Through the discovery learning model, students will be more active in the learning process. It can be concluded that students’ mathematical understanding abilities in online learning will be better if using Moodle-based media and with discovery learning models.